Indicadores de movimentos de conscientização de professores em processo de formação continuada em serviço - Benachio, Marly das Neves (2008)
The present essay intends to be a contribution to the in-service development program understood as a priority space of teacher formation in the school where teachers give their lessons. To understand the impact of this program, we chose as our case studies three teachers in this process of in-service development program of a private school in São Paulo city. We tried capture the subjective directions produced by these teachers on their teaching practice and then to point out awareness markers in these developing teachers. The Theory of the Subjectivity, by Fernando González Rey (2001, 2002, 2003, 2004, 2004a, 2005), together with the contributions by Aguiar (1997, 2001), Aguiar and Ozella (2006) helped us in this analysis which allowed us to understand the subjective directions expressed by the teachers. As reference for the development program we based our research on authors such as Placco (2000, 2000a, 2002, 2006, 2007, 2008), Almeida (2000, 2007), Gatti (1972, 2003), Nóvoa (1992), Marcelo Garci'a (1999, 2007), Mizukami et al (2003), Imbernón (2004) and Zeichner (1993, 1993a), amongst others. The methodology used is inserted in the paradigm of the qualitative research, having interviews as main source of information, besides some other tools such as short essays, choosing paintings by some known painters and observation. In the development process of the analysis, markers and meaning groups emerged making possible the acquisition of directions, from which we made the awareness markers of the teacher inserted in this program. These awareness markers are the subjective directions produced by the teachers in the sense of value to their teaching practice; emotions such as involvement, satisfaction, willingness; search for knowledge necessary for teaching; the value of spaces for the in-service development program; the confrontation and relationship between the coordinator and the teacher which should be based on respect, cooperation, focus on the professional. Getting to know Indicators of teachers awareness movement in the process of in-service continued education helps the coordinator/trainer to be more appropriately and efficiently supportive during the teachers development